Transcriptome analysis reveals the crucial function of hyperoside in inhibiting anthocyanin accumulation in grape (Vitis vinifera L.) fruits by inducing VvMYB62 - Su, Ling; Zhang, Man; Zhang, Yudie; Chen, Yingchun; Yang, Liying; Wang, Yongmei; Song, Yangbo; Gong, Lei (Frontiers in Plant Science, 2023)
Abstract The formation of color in plants is significantly dependent on anthocyanin pigments. Grape species vary in color due to the differences in anthocyanin accumulation. It is widely recognized that both biotic and abiotic conditions may have an impact anthocyanin synthesis in plants. The underlying molecular mechanisms by which external application of hyperoside impacts anthocyanin formation in grapes, however, have received little attention. In the current study, the transcriptome of Gemstone seedless grape was examined using high-throughput RNA sequencing at various developmental stages reply to both control and hyperoside treatments. The results of this study suggested that the major genes controlling anthocyanin accumulation in response to the external injection of hyperoside could be VvMYB62, VvPAL, VvCHS, and VvF3'5'H. Quantitative reverse transcription PCR (RT-qPCR) results were used to confirm the changes in the expression levels of the genes encoding the anthocyanin biosynthesis pathway under the ck and hyperoside treatments. Using a transient transformation system, it was discovered that VvMYB62 was shown to regulate the anthocyanin accumulation at both the transcriptional and posttranslational levels and could be influenced by the external administration of hyperoside. In grape embryogenic calli, hyperoside could specifically suppress the expression of VvMYB62 and anthocyanin accumulation. In this instance, the VvMYB62 characterisation brought attention to the significance of exogenous hyperoside-induced anthocyanin accumulation. Therefore, the results demonstrated that VvMYB62 could be hindered in the process of grape during anthocyanin accumulation caused by hyperoside. These findings offer excellent candidate genes in the future breeding of novel grape varieties in addition to serving as a crucial reference for understanding the underlying molecular processes of hyperoside suppression of anthocyanin formation in plants.